Liquiritigenin-loaded poly (acrylic acid)-carboxymethyl cellulose hydrogels: formulation optimization, performance evaluation, and assessment of therapeutic efficacy for wound healing and sepsis caused by wound bacterial infection - Meng, Xiang; Xue, Muzhou; Zeng, Zequn; Pei, Wenbin; Gong, Bing (Frontiers in Bioengineering and Biotechnology, 2026)
IntroductionBacterial wound infections that lead to sepsis pose a major clinical challenge. This study aims to develop and optimize a novel cross-linked poly(acrylic acid)/carboxymethylcellulose sodium (PAA/CMC-Na) hydrogel encapsulating liquiritigenin (LQ) to improve wound healing and infection control.MethodsThe hydrogel matrix was optimized using response surface methodology (RSM). Mechanical properties, self-healing efficiency, and pH-responsive swelling behavior were characterized. In vitro drug release profiles were evaluated over 24 h, and molecular docking simulations were performed to assess the binding affinity of LQ to key sepsis targets. Biological safety was tested using CCK-8 and Trypan blue assays, while anti-inflammatory and antibacterial activities were evaluated using LPS-stimulated RAW264.7 macrophages and pathogen inhibition assays (E. coli and S. aureus).ResultsThe optimized hydrogel achieved a high model fit (R2 = 0.976$) and exhibited superior mechanical performance, including 776% tensile strain and 100% self-healing efficiency. Swelling was pH-responsive (∼600% at pH 5.5 vs. ∼450% at pH 7.4). LQ showed sustained release (>90% over 24 hours) and strong binding affinity to sepsis-related targets. Biological assays confirmed high biocompatibility (>98% fibroblast viability). Furthermore, the hydrogel significantly reduced inflammatory cytokines (TNF-α, IL-6, IL-1β) in a dose-dependent manner and effectively inhibited the growth of E. coli and S. aureus.DiscussionThese findings demonstrate that the LQ-loaded hydrogel possesses excellent mechanical, biocompatible, and anti-inflammatory properties. Its dual-action as a pro-healing and antibacterial agent suggests it is a promising candidate for topical wound management and the prevention of infection-induced sepsis.